MENINGKATKAN MOTORIK HALUS DENGAN TEKNIK MELIPAT KERTAS PADA ANAK USIA 5-6 TAHUN DI RA AL-MA’SOEM CIAWI TASIKMALAYA - Nurhidayah, Nisa; Muthmainnah, Ai Siti; Setiawati, Elis (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2022)
This study aims to improve fine motor skills with paper folding techniques in children aged 5-6 years RA Al-Ma'soem Kp. Cibuyut district. Ciawi Kab. Tasikmalaya. This type of research is a collaborative classroom action research using the Arikunto model. The research subjects were Group B children, which consisted of 13 children consisting of 5 boys and 8 girls. The object of this research is fine motor skills. Data collection methods used are observation, documentation, and interviews. The instruments used are observation guidelines and interview guidelines. The data analysis technique was carried out in a qualitative descriptive manner. The success indicator that is set is if at least 75% of the 13 children have fine motor skills with good criteria. This research was conducted in two cycles. The results showed that the children's fine motor skills improved after the action through origami. At the time of pre-action observation, the percentage of children's fine motor skills was 15.4%. In the first cycle of 38.4% with an increase of 23%, in the second cycle of 84.6% with an increase of 46.2%. The percentage gain shows that the fine motor skills of children aged 5-6 years with good criteria have reached a success indicator of 75%. The steps taken to improve children's fine motor skills are 1) the teacher explains how to fold paper with the demonstration method; 2) children are given reinforcement; 3) the child is given a reward in the form of praise; 4) use colored folding paper to attract children's interest.